Surface Expression of Kynurenine 3-Monooxygenase Promotes Proliferation and Metastasis in Triple-Negative Breast Cancers. (22nd April 2021) - Lai, Min-Hua; Liao, Chi-Hsun; Tsai, Nu-Man; Chang, Kai-Fu; Liu, Cheng-Chi; Chiu, Yi-Han; Huang, Kuo-Ching; Lin, Chen-Si
Kynurenine 3-monooxygenase (KMO) is the pivotal enzyme in the kynurenine pathway and is located on the mitochondrial outer membrane. The dysregulation of KMO leads to various neurodegenerative diseases; however, it is rarely mentioned in cancer progression. Our previous study showed that KMO overexpression in canine mammary gland tumors (cMGT) is associated with poor prognosis in cMGT patients. Surprisingly, it was also found that KMO can be located on the cell membranes of cMGT cells, unlike its location in normal cells, where KMO is expressed only within the cytosol. Since cMGT and human breast cancer share similar morphologies and pathogenesis, this study investigated the possibility of detecting surface KMO in human breast cancers and the role of surface KMO in tumorigenesis. Using immunohistochemistry (IHC), flow cytometry (FC), immunofluorescence assay (IFA), and transmission electron microscopy (TEM), we demonstrated that KMO can be aberrantly and highly expressed on the cell membranes of breast cancer tissues and in an array of cell lines. Masking surface KMO with anti-KMO antibody reduced the cell viability and inhibited the migration and invasion of the triple-negative breast cancer cell line, MDA-MB-231. These results indicated that aberrant surface expression of KMO may be a potential therapeutic target for human breast cancers.